The Role of Inter-agency Collaboration in Managing Vagrancy and Begging: Insights from Makassar City - Ahmad, Roihan Rabil; Bulan, Tenry Zahra; HR, Sumayyah; Abdullah, Muhammad Nizar; Azmi, Ilima Fitri (KnE Social Sciences, 2025)
The high number of vagrants and beggars with various methods and tactics of operation remains a significant issue for the Makassar City government. Existing literature reveals that a lack of studies that comprehensively examine how this problem is addressed by local authorities. This qualitative research aims to describe the Makassar City government’s approach to managing vagrants and beggars by involving all relevant agencies. Data were collected through in-depth interviews, literature reviews, and direct observation, and analyzed using Edward III’s policy implementation theory. The findings indicate that current efforts remain short-term and lack a comprehensive strategy. The city’s policies focus on three main approaches: preventive guidance, educational guidance, and social rehabilitation. However, these efforts require stronger collaboration and synergy among stakeholders. The study recommends enhancing coordination among agencies and implementing more sustainable measures. Additionally, while it is important to maintain a humane approach, imposing social sanction or deterrents may be necessary to uphold public order.